Primary Adrenal Failure due to Antiphospholipid Syndrome - Murat Sahin; Ayten Oguz; Dilek Tuzun; Serife Nur Boysan; Bülent Mese; Hatice Sahin; Kamile Gul (Case Reports in Endocrinology)
Background. Antiphospholipid syndrome (APS) characterized by thrombosis and abortus may rarely cause primary adrenal failure. Case Presentations. A 34-year-old male presented with hypotension, hypoglycemia, hyperpigmentation on his skin and oral mucosa, scars on both legs, and loss of consciousness. In laboratory examinations, hyponatremia (135 mmol/L), hyperpotassemia (6 mmol/L), and thrombocytopenia (83 K/µL) were determined. Cortisol (1.91 µg/dL) and adrenocorticotropic (550 pg/mL) hormone levels were also evaluated. The patient was hospitalized with a diagnosis of acute adrenal crisis due to primary adrenal insufficiency. A Doppler ultrasound revealed venous thrombosis. The patient was diagnosed with antiphospholipid syndrome after the detection of venous thrombosis, thrombocytopenia, elevated aPTT, and anticardiolipin antibody levels. Anticoagulation treatment was started for antiphospholipid syndrome. The patient is now following up with hydrocortisone, fludrocortisone, and warfarin sodium. Conclusion. Antiphospholipid syndrome is a rare reason for adrenal failure. Antiphospholipid syndrome should be suspected if patients have morbidity secondary to venous-arterial thrombosis.